Pengaruh Uang Saku, Pembelajaran Akuntansi Keuangan dan Pengalaman Kerja Terhadap Perilaku Keuangan dengan Literasi Keuangan sebagai Variabel Intervening - Tyas, Eka Febi Wahyuning; Listiadi, Agung (Universitas Pendidikan Ganesha, 2021)
The financial behavior of each person is different as shown by the qualities of each individual. The study was directed to determine the results of the analysis of financial literacy to mediate the effect of pocket money, financial accounting learning, and work experience on financial behavior. Research location at the Universitas Negeri Surabaya with a research population of accounting education students at the Universitas Negeri Surabaya. Tests were carried out using purposive sampling technique and the sample size was determined using the Maholtra formula to obtain a total sample size of 120 respondents. The data collection methods were questionnaires and tests. With the Structural Equation Model data analysis technique using Warppls. So from the research results it can be seen whether there is no direct influence between pocket money on financial behavior. On the other hand, work experience and financial accounting learning variables have a positive and significant direct effect on financial behavior. Has a positive and significant influence between pocket money on financial literacy. Financial accounting learning variables and work experience have no effect on financial literacy. Financial literacy variables do not affect financial behavior and cannot mediate the effect of pocket money, financial accounting learning, and work experience on financial behavior.